2008
DOI: 10.1152/ajpregu.00039.2008
|View full text |Cite
|
Sign up to set email alerts
|

Claudin-3 tight junction proteins inTetraodon nigroviridis: cloning, tissue-specific expression, and a role in hydromineral balance

Abstract: Bagherie-Lachidan M, Wright SI, Kelly SP. Claudin-3 tight junction proteins in Tetraodon nigroviridis: cloning, tissue-specific expression, and a role in hydromineral balance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 41 publications
2
42
0
Order By: Relevance
“…Scott et al (21) proposed that reducing the paracellular loss of chloride was a probable mechanism contributing to population variation in FW tolerance in F. heteroclitus. The strong coordinated regulation of these genes in the gill is consistent with the immediate challenge of regulating paracellular ion loss when challenged with a hypoosmotic environment (22,23).…”
Section: Resultssupporting
confidence: 53%
“…Scott et al (21) proposed that reducing the paracellular loss of chloride was a probable mechanism contributing to population variation in FW tolerance in F. heteroclitus. The strong coordinated regulation of these genes in the gill is consistent with the immediate challenge of regulating paracellular ion loss when challenged with a hypoosmotic environment (22,23).…”
Section: Resultssupporting
confidence: 53%
“…In line S. P. Kelly and H. Chasiotis with this contention, both claudin-3 and -8 are considered to be barrier-promoting (or 'tightening') tight junction components in mammalian systems (Milatz et al, 2010;Yu et al, 2003). Furthermore, both claudins have previously been linked to epithelial tightening in the gills and kidney of fish (Bagherie-Lachidan et al, 2008;Bagherie-Lachidan et al, 2009;Duffy et al, 2011). However, in contrast to these observations, a primary cultured epithelium generated using puffer fish gill cells did not exhibit any alteration in claudin-8d mRNA abundance in response to cortisol treatment and, in the same preparation, claudin-3a transcript abundance decreased in response to cortisol (Bui et al, 2010).…”
Section: S P Kelly and H Chasiotismentioning
confidence: 81%
“…However, recent studies collectively suggest that the physiology of fish gill TJs is not straightforward (for review, see Chasiotis et al, 2012b), and a small number of reports further suggest that the molecular architecture and physiological properties of TJs in the skin of adult teleosts may also be complex and perhaps more environmentally responsive than might have been expected (Bagherie-Lachidan et al, 2008;Bagherie-Lachidan et al, 2009;Loh et al, 2004). In a comprehensive analysis of the claudin (Cldn) family of TJ proteins in Fugu (=Takifugu) rubripes, Loh et al (Loh et al, 2004) reported the presence of at least 32 cldn genes in gill Claudin-6, -10d and -10e contribute to seawater acclimation in the euryhaline puffer fish Tetraodon nigroviridis Phuong Bui and Scott P. Kelly* tissue, while other TJ proteins such as occludin and ZO-1 have also been described in gills of fishes such as Atlantic salmon (Tipsmark and Madsen, 2012), goldfish (Chasiotis and Kelly, 2008;Chasiotis et al, 2009;Chasiotis and Kelly, 2011a;Chasiotis and Kelly, 2011b), killifish (Whitehead et al, 2011), rainbow trout (Chasiotis et al, 2010;Kelly and Chasiotis, 2011) and zebrafish (Clelland and Kelly, 2010;Kumai et al, 2011).…”
Section: Research Articlementioning
confidence: 99%
“…However, in the initial phase of the study, it was found that cldn-6, -10d and -10e were also selectively present in the skin of T. nigroviridis. Given that the skin, like the gill epithelium, is exposed directly to surrounding water, and that recent evidence suggests that some Cldns may be responsive to salinity change in the integument of fish (Bagherie-Lachidan et al, 2008;Bagherie-Lachidan et al, 2009), it was considered reasonable to also examine the characteristics of epidermal Cldn-6, -10d and -10e in different ionic environments.…”
Section: Research Articlementioning
confidence: 99%
See 1 more Smart Citation